Determinants of Internal Control System on the Financial Performance of Rural and Urban Land and Building Tax (PBB-P2) at the Regional Tax and Retribution Management Agency (BPPRD) of Jambi City - Tegar Zaki Hanafi; Ratih Kusumastuti; Fredy Olimsar (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the influence of control environment, risk assessment, control activities, information and communication, and monitoring on financial performance. The research employs a descriptive quantitative approach. The sample selection was conducted purposively based on specific criteria. Primary data were collected through questionnaire distribution. Data analysis was performed using descriptive statistics and multiple linear regression with the assistance of SPSS software. The results indicate that, simultaneously, these factors have a positive and significant effect. However, partially, the control environment, risk assessment, and control activities do not have a significant impact on financial performance. Meanwhile, information and communication, as well as monitoring, have a positive and significant effect on financial performance.